Artothek 1973-1998. - Dinges, Christiane; Eickhoff, Beate; Euler-Schmidt, Michael; Fehlemann, Sabine; Hafif, Marcia; Hosmann, Barbara; Jonas-Edel, Justus; Kisters, Jürgen; Koerver, Jens Peter; Müller, Sabine; Plath, Carina; Schneider, Bruno F.; et al. (Köln : Wienand, 1998)
Wickramasinha, Marlini ; Horky, Ulla ; Kühl, Eva ; Desgranges, Claudia ; Hessling, Rosa M. ; Below, Peter ; Sims, Phil ; Weber, Heike ; Keusen, Ellen ; Kalinbach, Siglinde ; Joachim, Dorothea ; Buckley, Rick ; Hafif, Marcia ; Dederichs, Martha ; Brand, Five Star ; Dunst, Heinrich ; Brosch, Helmut ; Riedel, Tilo ; Lochmüller, Stefan ; Schulze, Andreas Karl ; Binding, Heiner ; Hasucha, Christian ; Kaiser, Raymund ; Weggenmann, Markus ; Frohnapfel, Doris ; Guttormsen, Signe
biografie
Duits
boek